Medication-Induced Gastroparesis: A Case Report - M Ammar Kalas MD; Gian Marco Galura MD; Richard W. McCallum MD, FACG, FACP (SAGE Publishing, 2021)
Gastroparesis is a commonly diagnosed gastrointestinal disorder with a high prevalence globally and high disease burden to those afflicted with it. Etiologies are variable with idiopathic and diabetes being the most common causes of gastroparesis. Management of gastroparesis depends on the etiology, and accurate diagnosis is required for better targeted therapy. Medication-induced gastroparesis is reversible, and discontinuing the medication is generally curative. This case report discusses 2 cases of medication-induced gastroparesis which were initially diagnosed as diabetic gastroparesis, and thorough history taking revealed the cause to be medication induced. Repeat studies following medication discontinuation revealed improvement in symptoms and resolution of gastroparesis. Further research needs to be done to assess the frequency of misdiagnosing diabetic patients with gastroparesis due to medications, specifically glucagon-like peptide-1 receptor agonists which are increasingly being used in diabetics.